Dermoscopic patterns of melanocytic nevi in children and adolescents: a cross-sectional study - Christiane Donato Piazza; Sergio Yamada; Aline P Marcassi; Marina G Maciel; Maria P Seize; Silmara C P Cestari (Sociedade Brasileira de Dermatologia, 2017)
Abstract Background: Childhood is a dynamic period regarding nevogenesis. Dermoscopy is a noninvasive technique, recommended for the evaluation of pigmented cutaneous lesions. Objectives: The purpose of this study was to describe the structures and dermoscopic patterns of melanocytic nevi observed in children and adolescents. Methods: Dermoscopy with photographic documentation was used for nevi located on the face, trunk, and extremities of 38 patients aged from one to 16 years examined at the Pediatric Dermatology Outpatient Clinic of the Federal University of São Paulo. Results: The study included 201 skin lesions that were diagnosed as nevi during clinic examination. Upon evaluation of the global dermoscopic pattern of the lesions, the most frequently observed nevi were reticular (39.0%), followed by homogeneous (23.9%) and globular nevi (16.4%). During evaluation of the dermoscopic structures, according to the body site, the pigment network was the most observed in the extremities. Study limitations: A limitation to be considered is that the inclusion of small or new lesions may hinder the differentiation between dots and globules. Conclusions: In our study, the most observed pattern was reticular. There was a difference in the predominance of structures dependent on the anatomical location.